PENGARUH PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII MTsN MODEL PADANG - Pebriani, Gita; Helendra, Helendra; Maizeli, Annika (Pendidikan Biologi, 2013)
ABSTRACTÂ The learning process of Natural Science at MTsN Model Padang seemed to be monotonous. This had led the students to get low achievement in Natural Science class. One of the causes was the teacher who rarely used attractive learning model which made the students got low interest and motovation to learn. To trigger the studentsâ activeness and motivation to learn, Student Facilitator and Explaining learning model was applied. The purpose of this research was to reveal the the effectÂ  of Â using Â Student Â Facilitator and Â Explaining learning Â modelÂ  on Â the Â studentsâ Â learning achievement in Natural Science in class VIII of MTsN Model Padang.This was quasi experimental research which used Randomized Control Group Posstest Only Design. The population of the research was all of students in class VIII of MTsN Model Padang registered in Academic Years 2013/2014. By using Purposive Sampling technique, class VIII4 was chosen as the experimental class, and class VIII9Â  was taken as the control class. The data of the research was in the form of aspects. The data was collected through observation. The data gotten then was analyzed by using normality, homogeneity, t nd tâ tests.Based on the result of the posttest, it was found that the average score of the students in cognitive aspect in the experimental class (79,37) was higher than that of tudents in the control group (71,28). The result of t-test showed that the value of tcalculated (2,94) was higher than ttableÂ  (1,67) indicating that the hypothesis wass accepted. The average score of the students in affective aspect in the experimental class (80,7) was higher than that of tudents in the control group (67,9). The resultÂ  of Â tâ-test Â revealedÂ  tht Â the Â value Â of Â tcalculatedÂ  Â (3,61) Â was Â higher Â thanÂ  that Â of Â tudents in psychomotor aspect in the experimental group (77,8) was higher than that of students in the control group (61,41). The result of t-test indicated that the value of tcalculated (4,31) was higher than ttable (1,67) showing that the hypothesis was accepted. Based on these result, it was concluded that the use of Student Facilitator and Expalaining learning model could improve the studentsâ learning achievement in Natural Science in class VIII of MTsN Model Padang.